Research of reducing and emulsifying abilities of vegetable and fruit powder - Нєміріч, Олександра Володимирівна; Петруша, Оксана Олександрівна; Ясюченко, Олександр Сергійович; Дрозд, Наталія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2015)
The problem of investigating reducing and emulsifying abilities of cabbage powders, obtained by drying with the mixed heat supply at temperatures of 50 and 70°C, as well as spinach and banana powders of low temperature drying was considered in the paper. These methods allow to obtain a dried product with a moisture mass fraction of no more than 7 %, maximally preserve the nutritional value of the dried products and reducing ability. Dispersion of cabbage, spinach and banana powders was determined by a microscopic method. It was shown that the majority of the cabbage powder particles at drying temperatures of 50 and 70 °C have sizes of up to 40 microns - 75...85 % and only about 15...25 % - 60...100 microns. Powders obtained by low-temperature drying contain medium and large particles (over 40 microns) – 29 % in spinach and 47 % in banana. The structure of cabbage, spinach and banana powders was investigated using the microscopic method. It was shown that the powder cabbage obtained by MHS-drying at a temperature of 50 °C has more compacted particle structure (at magnification by 1000 times) than at 70 °C. Spinach powder is represented by separate small particles, banana powder - by spherical-shaped particles, uniform throughout the mass. The rehydration ability of powders was investigated. It was found that at the process duration of t£10 min, the behavior of vegetable and banana powders is characterized by intense swelling in water at 20 °C. After 30 min, the swelling process ends up and reaches a maximum value for the cabbage powder at 70 °C – 920 %, for the spinach powder – 380 %, cabbage powder of MHS-drying at 50 °C takes an intermediate value. The banana powder swells least of all. Powder cabbage of MHS-drying at 50 °C absorbs less water than at 70 °C. Spinach and banana powders have the WA (water amount) value by 2...3 times lower than the cabbage samples. Structural analysis of IR spectra of fresh vegetable and powders obtained after drying at temperatures of 50 and 70 °C was performed. Studies indicate minor changes in the chemical composition of the raw material during drying at temperatures of 50 °C and 70 °C. The regularities of increase in water retention, fat retention and emulsifying abilities of cabbage powder of MHS-drying at the process temperature increase was revealed: the sample shows high values of the studied parameters compared to the sample of MHS-drying at 50 °C. Spinach and banana powders show low values of these technological properties.